Haematological Indicators of Response to Erythropoietin Therapy in Chronic Renal Failure Patients on Haemodialysis: Impact of Angiotensin-Converting Enzyme rs4343 Gene Polymorphism - Hamdan Almaeen A; Mostafa-Hedeab G (Dove Medical Press, 2021)
Abdulrahman Hamdan Almaeen,1 Gomaa Mostafa-Hedeab2,3 1Pathology Department, Medical College, Jouf University, Sakaka, Kingdom of Saudi Arabia; 2Pharmacology Department, Health Sciences Research Unit, Medical College, Jouf University, Sakaka, Kingdom of Saudi Arabia; 3Pharmacology Department, Faculty of Medicine, Beni-Suef University, Beni-Suef, EgyptCorrespondence: Gomaa Mostafa-HedeabPharmacology Department, Medical College, Jouf University, Sakaka, Kingdom of Saudi ArabiaTel +966 534627393Email Gomaa@ju.edu.sa; gomaa_hedeab@yahoo.comPurpose: This is the first cross-sectional study studying the changes in haematological indicators of the response to recombinant human erythropoietin (rHuEPO) therapy in chronic renal failure (CRF) patients on haemodialysis (HD) stratified according to ACE G2350A (rs4343) gene polymorphism.Design: An observational cross-sectional study.Setting: Nephrology department and Biochemistry and molecular biology department, faculty of medicine, Cairo University.Patients: A total of 256 CRF patients on HD for at least six months (162 male and 103 female) and 160 healthy subjects (122 male and 38 female) were recruited in the current study after signing a consent form. ACE G2350A (rs4343) Insertion/Deletion (I/D) was tested, the association between ACE G2350A (RS4343) gene polymorphisms and patients response to rHuEpo was evaluated.Results: ACE G2350A (rs4343) I/D was the most prevalent genotype, while I/I genotype was the lowest prevalent among patient or control subjects included in the study. D allele is the most prevalent allele, either among patients or the control group. Hemoglobin (Hb) level in patients with I/I and Deletion/Deletion (D/D) genotype was significantly higher compared to those with I/D genotype (P = 0.012 and P = 0.005, respectively). Serum iron in the I/D genotype was significantly higher than those with either I/I or D/D genotype (P = 0.045 and P = 0.018, respectively). Angiotensin-converting enzyme (ACE) content, total leukocytic count (TLC), and soluble erythropoietin receptor (sEpoR) were independent predictors of Hb level. The ACE gene, TLC, and serum iron were the independent factors that may affect the Haematocrit (Hct) level. ACE G2350A (rs4343) gene polymorphisms may affect the HD patient's responses to rHuEPOs.Conclusion: In HD patients, screening for ACE G2350A (rs4343) gene polymorphisms before rHuEpo administration may help predict patient response.Keywords: angiotensin-converting enzyme rs4343 gene polymorphism, hemoglobin, erythropoietin, chronic renal failure, hemodialysis